THEORETICAL ASPECTS OF FORMATION OF INNOVATIVE BUSINESS MARKETING STRATEGIES OF BUSINESS ENTITIES (Development Service Industry Management, 2025)
The article highlights the relevance of forming innovative business marketing strategies in the context of digital transformation and increasing market competition. It is noted that traditional marketing models are losing effectiveness, while businesses require new approaches integrating digital tools, innovation, and adaptive management. The scientific problem is identified as the lack of unified theoretical foundations for developing effective innovative business marketing strategies, which complicates strategic adaptation to market changes. The study analyzes recent research by Ukrainian and international scholars in the fields of innovation, strategic management, marketing strategies, and entrepreneurship, which allowed for the formation of a conceptual and categorical basis for the research. The content of key terms such as "innovation," "strategy," "business marketing," and "innovative strategy" is clarified. Special attention is given to the definition of an innovative strategy as a managerial tool that ensures the coordination of innovations within the framework of an enterprise's strategic development.The author substantiates that business marketing in the digital era represents a complex system of market interaction, where innovations function not only as tools for attracting clients but also as means of creating new competitive advantages. It is established that an effective innovative strategy has an interdisciplinary nature and requires the integration of digital technologies, marketing analytics, entrepreneurial thinking, and strategic management. As a result, the author proposes an original definition of the process of forming innovative business marketing strategies and presents a logical-structural model of the key research categories.
Keywords: innovation; strategy; innovation strategy; business; marketing; business marketing; innovative business marketing strategies